2015
DOI: 10.1159/000435815
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Poly-(ADP-Ribose) Polymerase Protects the Kidney in a Canine Model of Endotoxic Shock

Abstract: Poly-(ADP-ribose) polymerases (PARPs), a super family of enzymes, play important roles in preserving genomic integrity, regulating transcriptions, protecting telomeres and determining cell fate. PARP overactivation leads to metabolic disorder and cell injury via depletion of energy substance. However, it is still unclear whether PARP overactivation happens during acute kidney injury (AKI) caused by endotoxic shock (ES). Here, we built a canine model of lipopolysaccharide-induced ES to explore the role of PARP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…Besides tubulotoxicity and renal IRI, animals challanged with intravenous and intratracheal lipopolysaccharide as a model of (pneumo)sepsis-mediated renal failure developed acute tubular necrosis that was prevented partly by different PARP-1 inhibitors. [111][112][113] This is in some contrast to our own unpublished results in which the PARP1-inhibitor olaparib did not reduce renal IRI in our standard model. However, the importance of PARP-1 in glomeruli was shown by Jog et al 114 In their study, the investigators induced anti-glomerular basement membrane nephritis in Parp1 -/-mice and subjected lupus-prone mice to pharmacologic PARP-1 inhibition, and in both models they observed a protective effect of PARP-1 inhibition on the progression of necrotic glomerular lesions, renal function, and autoantibody formation (anti-double-stranded DNA and antichromatin antibodies in the latter model).…”
Section: Parthanatos In Renal Diseasescontrasting
confidence: 99%
“…Besides tubulotoxicity and renal IRI, animals challanged with intravenous and intratracheal lipopolysaccharide as a model of (pneumo)sepsis-mediated renal failure developed acute tubular necrosis that was prevented partly by different PARP-1 inhibitors. [111][112][113] This is in some contrast to our own unpublished results in which the PARP1-inhibitor olaparib did not reduce renal IRI in our standard model. However, the importance of PARP-1 in glomeruli was shown by Jog et al 114 In their study, the investigators induced anti-glomerular basement membrane nephritis in Parp1 -/-mice and subjected lupus-prone mice to pharmacologic PARP-1 inhibition, and in both models they observed a protective effect of PARP-1 inhibition on the progression of necrotic glomerular lesions, renal function, and autoantibody formation (anti-double-stranded DNA and antichromatin antibodies in the latter model).…”
Section: Parthanatos In Renal Diseasescontrasting
confidence: 99%
“…PARP over-activation consumes most of the intracellular NAD+, causing ATP storage to fulfill the huge energy demand and finally leading to cell dysfunction [33, 34]. In some other studies, PARP activation was inhibited, and the low activation of PARPs was widely considered to help cells avoid apoptosis under stress [24, 35]. Thus, we further focused on how PARP-1 inhibition could protect thyroid cancer cells from 131 I injury.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cell death was related to the extent of ATP depletion: a medium ATP decrease may cause cell apoptosis and a severe ATP decrease may lead to cell necrosis [36, 37]. Similarly, Yang found that PARP-1 inhibition with 3-AB may protect renal cells from apoptosis in hemodynamic disorders during an acute kidney injury mode through ATP restoration [35]. The above results implied that PARP-1 overactivation caused by 131 I radioactivity was accompanied by ATP crisis, triggering cancer cell death because of energy depletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(reviewed in Jagtap and Szabo, 2005) and is comparable to the effect of other, earlier-generation PARP inhibitors, as well as genetic PARP1 deficiency in various models of critical illness and systemic inflammation (Jagtap et al, 2002;Liaudet et al, 2002;Soriano et al, 2002Soriano et al, , 2006Shimoda et al, 2003;Farivar et al, 2004;Szabo, 2007;Wang et al, 2013;Liu et al, 2015;Walko et al, 2015;Zhang et al, 2015). Thus, olaparib -although originally developed and optimized for the purposes of cancer therapy -performs as expected as a PARP inhibitor in the context of inflammation, organ injury and critical illness.…”
Section: Figurementioning
confidence: 97%